Quizwhizzer as A Innovative Evaluation Learning Media Bahasa Indonesia - Uliana Hidayatika; Didah Nurhamidah (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2024)
This article discusses digital learning media in the form of game quizzes, namely Quizwhizzer as an innovative Indonesian language learning evaluation media. The method used is a descriptive qualitative method. Data collection uses a questionnaire technique with closed and open questions using Google Form media. The subjects of this research were 37 students of class XI IPA 1 MAN 1 Tangerang. Explanatory text material was used in the questions that researchers created on QuizWhizzer. Based on the results of data analysis, it was found that 36 students (97.3%) stated that answering Indonesian language questions was more interesting using Quizwhizzer than using sheets of paper. Furthermore, as many as 37 students (100%) stated that Quizwhizzer was an innovative and fun medium. Furthermore, as many as 33 students (89.2%) stated that Quizwhizzer could make it easier for students to understand Indonesian language material. Furthermore, as many as 34 students (91.9%) stated that Quizwhizzer was able to increase students' interest in learning Indonesian language material. Furthermore, as many as 36 students (97.3%) answered that Quizwhizzer was easy to use. Furthermore, as many as 35 students (94.6%) stated that the Quizwhizzer learning media was not boring. Furthermore, as many as 35 students (94.6%) stated that the Quizwhizzer learning media was not difficult. Finally, 31 students answered that their impression after using QuizWhizzer was that it was exciting, fun and happy. So it can be concluded that the digital interactive game media, namely Quizwhizzer, is an innovative evaluation media and attracts students' attention.